STUDY OF INLAND WATERWAY TRANSPORT ROUTING OPTIONS UNDER CONDITIONS OF UNCERTAINTY IN NAVIGATIONAL RESTRICTIONS - Velizara PENCHEVA; Asen ASENOV; Ivan GEORGIEV; Boril IVANOV; Ivelin ZANEV (Transport Problems)
Given the uncertainty of the navigating conditions on the Danube River, the hydrological situation on the Bulgarian leg of the river is predicted using ARIMA methods. The forecast is based on statistical daily hydrological data for a period of five years. A mathematical routing model is developed under the condition that it is not possible for a self-propelled vessel to continue its voyage due to draft limitation. Options including waiting for navigation opening, partial lightening on a barge, and a complete or partial modal shift to rail or road transport through an alternative port are considered. An acceptable option is determined, taking into account the additional costs and transit time. A routing simulation is made using SPSS software.